Responses of aerosol optical properties and direct radiative effects to rapid shifts in anthropogenic emissions in the sichuan basin - Fengjun Shen; Jie Sun; Guiying You; Jiaxin Wei; Xinlei Lv; Qiqi Mo; Tong Liu; Miao Feng; Yanyi Feng; Shaodong Xie; Gang Zhao; Min Hu (Environmental Pollution, 2026)

Overview of functionally characterized two-component regulatory systems in Vibrio parahaemolyticus - Fengjun Sun; Pu Yao; Yiquan Zhang (Archives of Microbiology, 2026)

Amplified radiative effects of coated black carbon aerosols over the Tibetan Plateau - Jie Sun; Gang Zhao; Jinyuan Yu; Weili Lin; Yi Chen; Chunxiang Ye; Wenxu Fang; Wenhao Zhou; Baifeng Zhu; Jiawei Yang; Zhijun Wu; Tong Liu; et al. (Atmospheric Research, 2026)

Development and characterization of a walnut protein hydrolysate-Fe-vitamin C complex: Enhancing iron bioavailability through phytase-assisted modification - Sibao Zhao; Wenzhen Qiu; Yang Sun; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Responsive packaging that adapted to and regulated physiological metabolic of fruits and vegetables: Mechanism, application and prospects - Chunjun Chen; Yibing Ding; Yucong Feng; Xiulian Li; Chanchan Sun; Fengjun Guo; Xiangquan Zeng; Hansheng Gong; Xinguang Fan (Trends in Food Science & Technology, 2025)

Low-field NMR-based deep learning for non-destructive quality assessment of frozen model foods - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun; Cuirong Ren (Food Chemistry, 2025)

Preparation of emulsions with resveratrol to form functional coatings: Effect on yellowing of frozen limes during storage - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun (Food Hydrocolloids, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

Host-derived lactic acid bacteria alleviate short beak and dwarf syndrome by preventing bone loss, intestinal barrier disruption, and inflammation - Mandi Liu; Fengjun Xiang; Jialu Pan; Yongzhi Xue; Maoyuan Sun; Kuan Zhao; Wuchao Zhang; Baishi Lei; Peipei Gao; Limin Li; Wanzhe Yuan (Veterinary Microbiology, 2024)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

Sedimentary Environment, Tectonic Setting, and Uranium Mineralization Implications of the Yimin Formation, Kelulun Depression, Hailar Basin, China - Fanmin Meng; Fengjun Nie; Fei Xia; Zhaobin Yan; Da Sun; Wenbo Zhou; Xin Zhang; Qing Wang (Journal of Marine Science and Engineering, 2024)
The sandstone-type uranium deposit of the Kelulun Depression is the first industrially valuable uranium deposit discovered in the Hailar Basin. This study performed a systematic examination of 17 sandstone samples from the Yimin Formation in the Kelulun Depression based on various analytical techniques. The findings of the current study were synthesized with previous research to investigate the impact of the redox conditions and the tectonic background of the source area, as well as the paleoclimatic evolution of the Yimin Formation on uranium mineralization. The elemental Mo, U/Th, V/Cr, Ni/Co, and V/(V + Ni) ratios indicate that the paleowater was in an oxygen-rich environment during the deposition of the Yimin Formation. Additionally, the C-value, Sr/Cu, Al2O3/MgO, and Rb/Sr ratios indicate that the Yimin Formation was formed in a paleoclimate characterized by arid-to-semi-arid conditions. The geochemical characteristics of the observed elements indicated that the sediment source of the Yimin Formation was mainly felsic rocks from the upper continental crust, the weathering of the rock was weak, and the tectonic background was a passive continental margin. Coffinite is distributed in the form of cementation and stellates within or around pyrite crystals, and uranium-titanium oxide is mostly distributed in an irregular granular distribution in the biotite cleavage fractures of the study area. In summary, the findings of this study reveal that the tectonic settings, provenance, uranium source, paleoclimate, and oxygen-rich paleowater of the Yimin Formation have important geological significance for the large-scale uranium mineralization of the Kelulun Depression.

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Path dependence or path creation of mature resource-based cities: A new firm entry perspective - Huijuan Sun; Li Ma; Fengjun Jin; Yujin Huang (Journal of Geographical Sciences, 2024)

2D flake-like garnet electrolytes for solid-state lithium metal batteries - Jun Cheng; Yixuan Guo; Hongqiang Zhang; Fengjun Ji; Xuan Zhou; Zhen Zeng; Hongbin Liu; Qing Sun; Deping Li; Lijie Ci (Chemical Engineering Journal, 2024)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Role of Penicillin-Binding Protein 1b in the Biofilm Inhibitory Efficacy of Ceftazidime Against Escherichia coli - Fengjun Sun; Yixuan Sun; Yu Wang; Qian Yuan; Lirong Xiong; Wei Feng; Peiyuan Xia (Current Microbiology, 2022)

Spatio-temporal Characteristics and Geographical Determinants of Air Quality in Cities at the Prefecture Level and Above in China - Zhe Sun; Dongsheng Zhan; Fengjun Jin (Chinese Geographical Science, 2019)

The effect of straw mulch on nitrogen, phosphorus and potassium uptake and use in hybrid rice - Fengjun Yan; Yongjian Sun; Xu Hui; Mingjin Jiang; Kaihong Xiang; Yunxia Wu; Qiao Zhang; Yuan Tang; Zhiyuan Yang; Yuanyuan Sun; Ma Jun (Paddy and Water Environment, 2019)

Effects of wheat straw mulch application and nitrogen management on rice root growth, dry matter accumulation and rice quality in soils of different fertility - Fengjun Yan; Yongjian Sun; Hui Xu; Yaozhu Yin; Haiyue Wang; Chunyu Wang; Changchun Guo; Zhiyuan Yang; Yuanyuan Sun; Jun Ma (Paddy and Water Environment, 2018)

A monocentric centerline extraction method for ring-like blood vessels - Fengjun Zhao; Feifei Sun; Yuqing Hou; Yanrong Chen; Dongmei Chen; Xin Cao; Huangjian Yi; Bin Wang; Xiaowei He; Jimin Liang (Medical & Biological Engineering & Computing, 2018)

Spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China - Xujia Cui; Zhibao Dong; Hu Sun; Chao Li; Fengjun Xiao; Zhengyao Liu; Shaopeng Song; Xiaolan Li; Nan Xiao; Weiqiang Xiao (International Journal of Climatology, 2018)
Research on the wind environment provides an important reference for tackling desertification and related environmental issues in desert regions. This article examines spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China, using data from 40 meteorological stations inside and around the dune fields. Wind speed series were first subjected to homogenization, with monthly mean wind speed of the highly correlated neighbour stations as reference series. We found that the homogenized wind speed trends were approximately in accordance with the raw wind speed trends. The wind environment showed spatial and temporal differences, but wind speed has generally decreased both annually and seasonally since 1960, with an average trend of −0.193 m s −1 decade −1 . Mean wind speed (1960–2014) and maximum wind speed (1975–2014) decreased significantly, with distinct seasonal differences. The decreasing trend depended strongly on a decreased wind of speeds >5 m s −1 and its frequency. Overall, 48.7–80.8% of the decrease resulted from decreases in the maximum wind speed. Thus, decreases in the maximum wind speed were the dominant change in the study area. We also found that two thirds of the decrease in the drift potential primarily resulted from decreases in three prevailing wind groups (northwest, west, and south winds). This resulted from changes in the East Asian monsoon and westerly circulation. Mean air and ground surface temperatures (1960–2014) increased significantly and were significantly negatively correlated with mean wind speed, whereas sunshine duration (1960–2014) decreased significantly and was significantly positively correlated with mean wind speed. Both correlations reveal that an increasing of atmospheric dust may be responsible for the weakened wind environment. However, China's widespread sand‐control and ecological construction projects have increased ground roughness.

The Master Quorum-Sensing Regulator OpaR is Activated Indirectly by H-NS in Vibrio parahaemolyticus - Yiquan Zhang; Lingyu Zhang; Shuning Hou; Xinxiang Huang; Fengjun Sun; He Gao (Current Microbiology, 2016)

CRP Acts as a Transcriptional Repressor of the YPO1635-phoPQ-YPO1632 Operon in Yersinia pestis - Yiquan Zhang; Fengjun Sun; Huiying Yang; Lei Liu; Bin Ni; Xinxiang Huang; Ruifu Yang; Dongsheng Zhou (Current Microbiology, 2015)